2013
DOI: 10.1007/s10584-013-0911-4
|View full text |Cite
|
Sign up to set email alerts
|

Tall tales and fat tails: the science and economics of extreme warming

Abstract: It has recently been highlighted that the economic value of climate change mitigation depends sensitively on the slim possibility of extreme warming. This insight has been obtained through a focus on the fat upper tail of the climate sensitivity probability distribution. However, while climate sensitivity is undoubtedly important, what ultimately matters is transient temperature change. A focus on transient temperature change stresses the interplay of climate sensitivity with other physical uncertainties, nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…However, the implementation in [63] is not strictly causal in that the atmospheric temperature at the next time step depends on the radiative forcing at the next time step. This was previously observed in [11] and [12]. We explicitly provide the derivation of the model here for future reference.…”
Section: Climate Modelsupporting
confidence: 57%
“…However, the implementation in [63] is not strictly causal in that the atmospheric temperature at the next time step depends on the radiative forcing at the next time step. This was previously observed in [11] and [12]. We explicitly provide the derivation of the model here for future reference.…”
Section: Climate Modelsupporting
confidence: 57%
“…It is worth emphasising, before moving on to the results, that there are other potentially significant sources of risk attending to the impacts of greenhouse gas emissions. Some of these are in the climate system – for instance the effective heat capacity of the oceans (Calel et al ., ) – yet a focus on S captures the essence of physical climate risk in a clear and simple way. Other sources of risk relate to damage for any given temperature and could also be modelled with probabilities, were the evidence to justify doing so.…”
Section: Extending Dicementioning
confidence: 99%
“…where F t is radiative forcing, F 2ÂCO 2 is the radiative forcing resulting from a doubling in the atmospheric stock of carbon dioxide, S is the climate sensitivity, T LO is the temperature of the lower oceans, j 1 is a parameter determining speed of adjustment and j 2 is the coefficient of heat loss from the atmosphere to the oceans. Calel et al (2014) contains a detailed explanation of the physics behind this equation.…”
Section: Climate Riskmentioning
confidence: 99%
“…The third line of research has focused on exploring economic and physical uncertainties in IAMs through the use of Monte Carlo methods: Ackerman et al (2010) explored the implications of varying simultaneously the climate sensitivity parameter and the damage function exponent using the DICE model; Pycroft et al (2011) conducted a similar exercise using PAGE09; Calel et al (2013) demonstrated that the uncertainty about the effective heat capacity of the upper ocean mattered significantly for economic evaluations.…”
Section: Introductionmentioning
confidence: 99%